Methods for community-based participatory research for health - Eugenia, Eng; Israel, Barbara A.; Parker, Edith A.; Schulz, Amy J. (Jossey-Bass, 2013)
"This thoroughly revised and updated second edition provides a step-by-step approach to application of participatory approaches to qualitative data collection (including structured and unstructured interviews, observations, and group interviews) and data analysis (including constant comparative method, coding schemes, and theme memo). Some of the methods included are: survey questionnaire, in-depth interview, focus group interview, ethnography, exposure assessment, and geographic information system mapping. This book brings together many of the leading scholars who are teaching and conducting CBPR in health and related fields to provide readers with strategies and lessons learned for how to apply different methods using a partnership approach"